THE INFLUENCE OF ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE AT BUNGONG JAROE PLAYGROUND AND RESTAURANT - hajar, elvira sitna (BAIK Publishers, 2024)
The purpose of this study was to determine the effect of organizational culture on employee performance at Bungong Jaroe Playground and Restaurant. The research method used in this study uses a quantitative approach. The population is 44 people. The sampling technique uses saturated samples so that the number of samples in this study is 44 respondents. The data analysis technique uses simple linear regression. The results of the study show that there is a positive and significant effect of the effect of organizational culture on the employee performance at Bungong Jaroe Playground and Restaurant. This is evidenced by the tcount > ttable value, namely 7.785 > 2.018 with a probability value (significance) = 0.000, which is below 0.05.